Social influence among rural youth in using the rural library services in Malaysia - Bolong, Jusang; Omar, Siti Zobidah; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Asian Network for Scientific Information, 2015)
The main attempt of this study is to identify the social influence among the youth that might impinge them to go and use the rural library services offered at their areas. This was a quantitative study where a developed questionnaire was used in the data collection process. The study was conducted at Johor, Terengganu, Kedah and Perak and involves a total of 400 rural youth aged between 15-40 years old. The analysis performed that all of the social sources listed recorded a high level of mean score whereby good communication with rural library staffs recorded the highest mean score while encouragement from village leaders recorded the lowest mean score. A number of recommendations were placed and hoped that such recommendations can assist the concerned parties in constructing strategic planning for rural library development.